Administering Neostigmine as a Subcutaneous Infusion: A Case Report of a Patient Dying With Myasthenia Gravis. Issue 2 (April 2020) - Hindmarsh, Jonathan; Woods, Elizabeth; Lee, Mark; Pickard, Jonathan
Background: Abrupt withdrawal of pharmacological therapies for myasthenia gravis can exacerbate muscle weakness and even trigger myasthenic crisis. Such medications should ideally be continued, but how this can be achieved in patients approaching the end of life, particularly when enteral administration is compromised, has not been defined. Case History: An 83-year-old man with a history of generalized myasthenia gravis and palliative metastatic anal adenocarcinoma was admitted to his local hospital with general decline, where he was considered by more than one physician to be actively dying from his cancer. In the days preceding admission, the patient had not taken his medications consistently, including the acetylcholinesterase inhibitor, pyridostigmine, for the management of his myasthenia gravis. Case Management and Outcome: Reintroduction of the patient's usual myasthenia therapy improved his clinical condition to the point where he was no longer thought to be dying. When enteral administration of pyridostigmine was no longer possible, the patient was successfully converted to neostigmine, which was administered as a continuous subcutaneous infusion. Conclusion: Undertreated myasthenia gravis can lead to a rapid deterioration in a patient's clinical condition, and such patients may be mistakenly diagnosed as dying. Undertreated myasthenia gravis should therefore be considered as a potentially reversible cause of acute deterioration, especially in patients with complex comorbidities. The use of neostigmine as a continuous subcutaneous infusion may have a role in the management of such patients, particularly when enteral administration of acetylcholinesterase inhibitors is no longer possible.